Compassion Stress and the Qualitative Researcher - Kathleen B. Rager (Qualitative Health Research, 2005)
Human subjects are carefully protected in the research process. However, the same consideration is not currently being given to the qualitative researcher, even those investigating topics that are likely to elicit powerful emotions. The role of researcher’s emotional responses and the self-care strategies that, in some circumstances, are appropriate for the researcher and other research support personnel have not received the attention they deserve in qualitative research literature. Based on experience in conducting research on the topic of self-directed learning and breast cancer, and on the limited literature available, the author makes the case for the use of strategies such as counseling, peer debriefing, and journal writing as means of dealing with the potential for “compassion stress” as experienced by the researcher and other research support personnel. She also suggests that the preparation of social science researchers should include information on appropriate self-care strategies.
Keywords: emotions and qualitative research; self-care strategies for researchers